2001
DOI: 10.2307/3345708
|View full text |Cite
|
Sign up to set email alerts
|

MENC 2000 National Biennial In-Service Conference: A Content Analysis

Abstract: The 413 sessions of the 2000 MENC National Biennial In-Service Conference were classified according to category, which included educational sessions, concerts and sessions that included performances, and general sessions. They were also grouped according to subject areas, including general music, performance, administration, research, technology, industry and exceptionalities. By far the largest proportionate category of sessions was education (65%), followed distantly by sessions including performances (17%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 4 publications
2
28
1
Order By: Relevance
“…Sessions dealing with multicultural issues occurred at all four conferences, with the largest representation (17%) at the Orff-Schulwerk conferences. As reported in previous conferences' analyses (Price & Orman, 1999, 2001, sessions relating to exceptionalities continue to be less than 1 % of the offerings at the MENC conferences. This was mirrored by the Orff-Schulwerk conferences, and no sessions for exceptionalities were found at the ACDA conventions or the Midwest conferences.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Sessions dealing with multicultural issues occurred at all four conferences, with the largest representation (17%) at the Orff-Schulwerk conferences. As reported in previous conferences' analyses (Price & Orman, 1999, 2001, sessions relating to exceptionalities continue to be less than 1 % of the offerings at the MENC conferences. This was mirrored by the Orff-Schulwerk conferences, and no sessions for exceptionalities were found at the ACDA conventions or the Midwest conferences.…”
Section: Discussionmentioning
confidence: 76%
“…These exhibitors were primarily commercial entities offering some type of product or service for sale. Since previous research (Price & Orman, 1999, 2001) revealed a rise in industry presence within the sessions at the MENC national biennial conferences, we completed an analysis of the proportion of exhibitors from each of the four organizations' conferences in this study to gain a broader sense of the presence of industry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first article offered an overview of policy statements within NCLB regarding teacher professional development and suggested that "professional development is a foundation of NCLB and is cited quite often within its language" (2005a, 3). We then provided a literature review of all studies found in 2005 devoted to music teacher professional development-which numbered only four (Bowles 2002;Conway 2003; Music Educators National Conference [MENC] 2004; Price and Orman 2001). This article suggested a need for more research on professional development of arts educators and recommended that arts educators "be involved in the discussion regarding research of professional development and the definitions of scientific research" (2005a, 7).…”
Section: Overview Of Special Focus Issuementioning
confidence: 95%
“…Interestingly, enhancement of their own musicianship was not listed as a priority. Content analysis of the MENC: The National Association for Music Education national biennial in-service conferences from 1984-2000 revealed that from 1984 to 2000, the number of performance-oriented sessions decreased from 59.6% to 17.1% [4]. These findings are puzzling in light of the fact that "music teachers do not think of musicmaking and music teaching as two separate aspects of being music teachers.…”
Section: Introductionmentioning
confidence: 99%